The Comparison of Self-Concept and Death Anxiety Between Women Affected by Type 1 and 2 Diabetes and Healthy Women - Rahrovi 1, Ghoncheh; Nouhi 1*, Shahnaz; Khastar 2, Hossein (Shahroud Journal of Medical Sciences, 2018)
Background: Chronic disorders are those that entangle the patient for a long time and affect the person's ability for normal operation. What is important in the treatment of a chronic disease such as diabetes, in addition to controlling the disease, is improving patient's personal and psychic performances. The effect of diabetes and its complications on self-concept and anxiety of death are still unknown and studies in this field are insufficient. This study aimed to compare self-concept and death anxiety in type2diabetic and healthy women.Methods: The present study is a causal-comparative study. In this study from all diabetic women who were admitted to gynecology, dialysis and outpatients of Shahid Chamran Hospital, Tehran, Iran, and healthy women 30 to 60 years. 200 cases were selected using non-random purposive sampling in 2016.From this sample, 100 women with type 2 diabetes and 100 healthy women were selected based on entering standards. The questionnaire used in this study included Rogers Self-concept Inventory (1975) and Templer Death Anxiety Inventory (1970).Data was analyzed using descriptive statistics and inferential statistics methods (independent t-test and Chi-square test) using SPSS version 18.Results: The results showed that Rogers self-concept (B form) among women with type 2 diabetes(113.98±16.64) was significantly lower than among non-diabetic women (123.65±13.07) (P=0.003<0.05), Rogers self-concept (A form) did not have significant difference among diabetic (111.59±18.40) and non-diabetic women (114.24±13.17)(P=0.776) and death anxiety among women with type 2 diabetes (44.41±8.44) was significantly higher than among non-diabetic women (21.05±3.22) (P=0.005).Conclusions: Self-concept and anxiety of death may be considered as causes or risk factors or resonators in type 2 diabetes.